DHT (Diapers Hydrogel and Tajin) Fertilizer: Liquid Organic Fertilizer for the Growth of Chili Pepper Plants (Capsicum frustencens) - Mochammad Nasrul Hidayat (Jurnal Pijar MIPA, 2026)
The issue of disposable diaper waste is a significant environmental challenge because it is difficult to decompose, taking between 250 and 500 years, and leads to widespread pollution. The rising volume of diaper waste and the suboptimal disposal of rice wash water (air tajin) require innovative solutions. This research offers a novel approach by integrating the water retention capacity of diaper hydrogel with the nutritional benefits of rice wash water into a single Liquid Organic Fertilizer (LOF) formulation. A nutritional hydrogel derived from used diapers can absorb baby urine, which contains ammonia (approximately 60%) and urea (approximately 35%), both of which are essential nutrients for plants. DHT Fertilizer is created by extracting hydrogel from cleaned, used diapers. The hydrogel is heated to 50 °C for 60 minutes, then mixed with 60 mL of rice wash water. This study aims to repurpose these waste materials into "DHT Fertilizer" and test its effectiveness on the growth of bird's eye chili (Capsicum frutescens). Experimental Design: This quantitative experiment involved one control plant and one treatment plant, each with a single replication, and was observed over a two-week period. The independent variable was the dosage of DHT Fertilizer, and the dependent variable was the growth of the chili plants. The fertilizer was applied by spraying the plants twice daily, in the morning and evening. The results show that DHT Fertilizer significantly and rapidly increases the growth of bird's eye chili compared to the control plant. This accelerated growth is driven by the ammonia and urea content, while the vitamin B and E components from the rice wash water improve the plant’s resistance to weather changes. Additionally, the hydrogel component helps the plant absorb and store water efficiently. DHT Fertilizer serves as an eco-friendly, efficient, and easy-to-use solution to overcome growth vulnerabilities in chili plants.